Experimental Study on Crack Extension Rules of Hydraulic Fracturing Based on Simulated Coal Seam Roof and Floor - Lu Gao; Xiangtao Kang; Gun Huang; Ziyi Wang; Meng Tang; Xiaoying Shen (Geofluids)
Hydraulic fracturing can increase the fracture of coal seams, improve the permeability in the coal seam, and reduce the risk of coal and gas outburst. Most of the existing experimental specimens are homogeneous, and the influence of the roof and floor on hydraulic fracture expansion is not considered. Therefore, the hydraulic fracturing test of the simulated combination of the coal seam and the roof and floor under different stress conditions was carried out using the self-developed true triaxial coal mine dynamic disaster large-scale simulation test rig. The results show that (1) under the condition of triaxial unequal pressure, the hydraulic fractures are vertical in the coal seam, and the extension direction of hydraulic fractures in the coal seam will be deflected, with the increase of the ratio of the horizontal maximum principal stress to the horizontal minimum principal stress. The angle between the extension direction of the hydraulic fracture and the horizontal maximum principal stress decreases. (2) Under the condition of triaxial equal confining pressure, the extension of hydraulic fractures in the coal seam are random, and the hydraulic fracture will expand along the dominant fracture surface and form a unilateral expansion fracture when a crack is formed. (3) When the pressure in one direction is unloaded under the condition of the triaxial unequal pressure, the hydraulic fractures in the coal seam will reorientate, and the cracks will expand in the direction of the decreased confining pressure, forming almost mutually perpendicular turning cracks.